Cloning and overexpression of the DREB30 gene enhances drought and osmotic stress tolerance in transgenic potato - Qurat- Ul Ain-Ali; Faiza Munir; Muhammad Tahir; Rabia Amir; Alvina Gul (Journal of Plant Interactions)
Potato is an extremely important food crop due to its high nutritional and economic value; however, this crop suffers losses due to water-deficient conditions. The aim of the study was to analyze the expression profiles of the StDREB30 gene and to study the enzymatic antioxidant system of transgenic potatoes under water-deficient situations. The results depicted that following drought and 20% polyethylene glycol 6000 stresses, transgenic plants showed vigorous growth, increased antioxidant activities, low malondialdehyde, and enhanced differential expression of StDREB30 in transgenics compared to control plants. Results suggest that StDREB30 overexpression mitigated the negative effects of water-deficit treatments by reducing oxidative damage in plants. Hence, the StDREB30 gene retains extensive potential for crop bioengineering to generate highly tolerant crop plants.